Study on the Method of Technical Condition Evaluation Index Based on the Measured Results of Natural Frequency of Bridge Superstructure - Hao Zheng (Innovation in Science and Technology, 2024)
With the growth of bridge service periods and the gradual degradation of the function, and reasonable evaluation of its technical conditions, it is very important for maintenance decision-making. Especially for the bridge after some reinforcement disposal, the original structure does not have conditions in accordance with conventional detection, and it is more difficult to accurately grasp the actual working state of the bridge. The self-vibration frequency is an inherent characteristic of the bridge. When the bridge function declines, its structure rigidity decreases. In fact, the measurement of the self-vibration frequency also decreases accordingly, which directly reflects the working status of the bridge. Therefore, finding the relationship between the actual measurement results of the bridge autobiography and the level of its technical status can not only quickly grasp the working status of the bridge, but also reflect the hidden diseases that cannot be detected with conventional means, and can also be reflected by the self-vibration frequency. The technical condition evaluation method based on the measured results of natural frequency can provide reliable decision-making basis for bridge maintenance management department in bridge maintenance.